The inter-organizational linkages in the implementation of self-helping housing stimulant program - Candradewini, Candradewini; Rusli, Budiman; Adhy Muhtar, Entang (International Journal of Engineering and Technology, 2018)
Cirebon Regency is the regency that has the fastest implementation progress among the regencies/cities receiving the Self-Helping Housing Stimulant in West Java Province. The initial observations and interviews from this research indicate that one of the supporters of the development of this program is the good relationship between the parties involved in the implementation of this program. This study aims to explain inter-organizational linkages between the parties associated with this program. The research method used qualitative approach. Data and information is obtained through in-depth interview, observation and documentation study. The informants in this research are institutions related to the poor community housing improvement program consisting of local government, district government, village government and community in Klangenan District, Cirebon Regency. The result of the research explains that inter-organizational linkages among the parties that run the program of house improvement in Cirebon Regency is going well. The facilitators of this program are proactive in communicating and establishing working relationships with beneficiary communities. This condition is reinforced by the cultural value of "ngersaya," which is a value of life of the local population in the form of repayment and nurturing kinship with those who have helped. Nevertheless, there are still some problems and obstacles faced such as the intensity of face-to-face is still rare and coordination meetings that have not scheduled regularly, especially with the technical team of the Government of Cirebon Regency. This research found that cultural value has a significant role in inter-organizational linkages between parties.Â Â
Keywords: Inter-Organizational Linkages; Self-Helping Housing Stimulant Program